Design Study Co-Working Space Building Based On Bioclimatic Architectural Principles - Jovianti Maya Ayuni; Mohammad Pranoto Soedjarwo (Journal of Architectural Design and Urbanism, 2022)
Bioclimatic principles that provide solutions based on environmental conditions around the site can be applied in building design. This design study focuses on the suitability of bioclimatic principles applied to environmental conditions in providing thermal comfort. This research method uses a qualitative method with a descriptive approach. The analysis technique in data collection is visual assessment. The object of the building under study has building criteria with the Indonesian tropical concept. The results of the study concluded that the two objects had applied the principles of bioclimatic architecture, but the first object was still not maximized while the second object was quite optimal in responding to environmental conditions